Respuesta :

Answer:

f(x) = (8/3)x(x - 1).

Step-by-step explanation:

The vertex form of the function is

y = a(x - 1/2)^2 - 2/3   where a is some constant.

Now the roots are 0 and 1 so

For  x = 0

0 =  a(-1/2)^2 - 2/3

1/4 a = 2/3

a = 2/3 / 1/4  = 8/3.

So the function is

f(x) = (8/3)(x - 1/2)^2 - 2/3.

3 f(x) = 8(x - 1/2)^2 - 2

= 8(x^2 - x + 1/4) - 2

=  8x^2 - 8x + 2 - 2

3 f(x) = 8x(x - 1)

f(x) = (8/3)x(x - 1).

Answer: f(x)=(8/3)•(x-1)

Step-by-step explanation:

F(X)=A(X-1)(X-0)

F(X)=AX(X-1)

You need to find : A!!

(1/2,-2/3) is resting in Parabola : -2/3=A(1/2)(1/2-1)

(1/4A=2/3

A=(4)(2)/3=8/3

F(X)=(8/3)•(X-1)

I hope this helps!